The role of magnetic resonance imaging in evaluating postoperative ACL reconstruction healing and graft mechanical properties: a new criterion for return to play? - DeFroda, S. F.; ODonnell, R. M.; Fadale, P. D.; Owens, B. D.; Fleming, B. C. (The Physician and Sportsmedicine, 2021)
Background: Disruption of the anterior cruciate ligament (ACL) is a common injury. In active patients, it is routinely treated with ACL reconstruction surgery. Following reconstruction, one of the critical decisions that must be made is the optimal timing of return to sport. While many biomechanical, biological, and functional criteria have been proposed to determine return to play, these methods are limited at best.